Indian Priest and Temple near Arouca, Trinidad and Tobago, B.W.I. - Keith Simpson [Photographer] (Mike Roberts Colour Production, California, Distributed by M. Jolly, Trinidad, B.W.I., 2008)
This is a portrait of a Hindu priest standing in front of a temple. Postcard number C5563.
Colour: Blue, white and black; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; East Indians--Trinidad and Tobago; Hindu priests--Trinidad and Tobago; Hindu temples--Trinidad and Tobago; Trinidad and Tobago